Multiple thread ligations versus stapled hemorrhoidopexy on operative outcomes of grade III hemorrhoids: A retrospective cohort study - Zhou, Xile; Liu, Fanlong; Lin, Caizhao; Chen, Wenbin; Xu, Jiahe (Frontiers in Medicine, 2023)
Object: Controversy remains regarding the safety and efficacy of hemorrhoid ligation and stapled hemorrhoidopexy (SH) in the treatment of hemorrhoids. The study was to explore the operative outcomes of patients underwent multiple thread ligations (MTL) with SH for the management of grade III hemorrhoids. Methods: This cohort study included patients who underwent MTL (MTL group, 128 cases) or SH (SH group, 141 cases) for grade III hemorrhoids between June 2019 and May 2021. A total of 115 patients in MTL group and 115 patients in SH group were finally included by propensity score matching with a ratio of 1:1. The primary outcome was the recurrence of prolapse within six months. Secondary outcomes were operative time, postoperative pain scores, hospital stay, the incidence of complications, Wexner incontinence score, and quality of life of patients with constipation at six months post procedure. Results: MTL and SH resulted in comparable recurrence within six months of follow-up, with five and seven cases of recurrence respectively (P = 0.352). The two groups had comparable outcomes in terms of postoperative pain, hospital stay, Wexner incontinence scores, and constipation-related quality of life (all P > 0.05). The median operative time was 16 min (15–18 min) in the MTL group versus 25 min (16–33 min) in the SH group (P < 0.01). Univariate analysis showed that the MTL technique had a lower risk of postoperative bleeding than that with the SH technique (P < 0.05). Conclusion: The study indicated that the MTL technique might achieve comparable operative outcomes compared with the SH technique for the management of grade III hemorrhoids，nevertheless, MTL seemed to be associated with less risk of surgical bleeding than SH.